2002
DOI: 10.1096/fj.01-0890fje
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐inflammatory effects of tetrahydrobiopterin on early rejection in renal allografts: modulation of inducible nitric oxide synthase

Abstract: Oxidative stress contributes to the development of early transplant failure. As nitric oxide synthases (NOS) can act as sources of superoxide, we investigated the effect of the NOS cofactor tetrahydrobiopterin (BH4) on oxyradical production and early rejection in a rat kidney transplantation model. Allograft transplantation (Brown Norway to Lewis) showed more renal superoxide production and monocyte infiltration when compared with isografts (Lewis to Lewis). Administration of the stable BH4 precursor sepiapter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 48 publications
2
25
0
1
Order By: Relevance
“…23 Although several studies have now shown salutary effects of BH4 on endothelial function and eNOS regulation (reviewed in Alp et al 24 ), a potential role for BH4 in modulating vascular inflammation has been suggested by only one previous study, in a model of transplant rejection. 25 ROS have been implicated in initiating inflammatory responses through activation of signal transduction pathways such as mitogen-activated protein (MAP) kinases and phosphoinositide-3-kinases (PI-3-K) as well as redox-sensitive transcription factors, such as NF-⌲B and AP-1 leading to enhanced gene expression of proinflammatory mediators (reviewed in Kunsch et al 5 ). Among the multiple gene products regulated by these transcription factors involved in atherosclerosis is the CC-CK MCP-1.…”
Section: Ali Et Al Tetrahydrobiopterin Reduces Vascular Inflammation S75mentioning
confidence: 99%
“…23 Although several studies have now shown salutary effects of BH4 on endothelial function and eNOS regulation (reviewed in Alp et al 24 ), a potential role for BH4 in modulating vascular inflammation has been suggested by only one previous study, in a model of transplant rejection. 25 ROS have been implicated in initiating inflammatory responses through activation of signal transduction pathways such as mitogen-activated protein (MAP) kinases and phosphoinositide-3-kinases (PI-3-K) as well as redox-sensitive transcription factors, such as NF-⌲B and AP-1 leading to enhanced gene expression of proinflammatory mediators (reviewed in Kunsch et al 5 ). Among the multiple gene products regulated by these transcription factors involved in atherosclerosis is the CC-CK MCP-1.…”
Section: Ali Et Al Tetrahydrobiopterin Reduces Vascular Inflammation S75mentioning
confidence: 99%
“…Substantial elevations of NO can also contribute to formation of peroxynitrites and increased oxidative damage [23,24]. Although the urinary NO was higher in the REG diet males at 8 weeks compared to the AO diet males, this difference did not reach statistical significance, This may be due to the fact that urinary NO reflects the total circulating NO in addition to the renal NO.…”
Section: Discussionmentioning
confidence: 95%
“…NOS isoforms can act as sources of superoxide. All of these molecules can damage the mitochondria and cause cell death [23,24]. NO synthesized by eNOS plays an important role in maintaining renal blood flow following renal transplantation and therefore normal regulation of the NO system needs to be maintained [25].…”
Section: Introductionmentioning
confidence: 99%
“…This consideration requires that more studies are necessary to better understand the post-translational modification of NO production from iNOS by tetrahydrobiopterin in transplant rejection. This concept is inferred from other recent findings in a renal transplant model in which supplementation with sepiapterin to increase levels of biopterin via the salvage pathway increased NO content and decreased superoxide production [149]. It was not clearly determined; however, that iNOS was the source of superoxide production in renal rejection and the improved NO production following treatment with sepiapterin occurred via iNOS or constitutive NOS.…”
Section: Post-translational Regulation Of No Bioactivity From Inosmentioning
confidence: 95%